982. Formal Education Improves Southeastern United States Primary Care Residents' Understanding and Attitudes Towards HIV Pre-Exposure Prophylaxis: Results of a Regional Survey. (31st December 2020) - Weaver, Christian D; Mena, Leandro A; Ward, Lori M
Abstract: Background: HIV pre-exposure prophylaxis (PrEP) has been identified as one of the pillars of the national plan to end the HIV epidemic. Notably, southern states have also been shown to have the lowest PrEP-to-need ratio in the country, and previous work on assessing clinician understanding of and attitudes towards PrEP has mainly focused on in-practice physicians, nurse practitioners, and other clinicians. We aimed to assess the attitudes towards and understanding of PrEP among residents training in programs categorized as primary care in the Southeastern United States. Methods: Program directors in ACGME approved residency programs in Family Medicine, Internal Medicine, Internal Medicine-Pediatrics, and Obstetrics and Gynecology were asked to distribute an invitation with a link to the survey to their residents during a six week period in May and June 2019. The survey contained questions that assessed demographics, type of program, PrEP awareness, knowledge, attitudes, and formal education Logistic regression was utilized to assess association between formal PrEP education and comfort levels with PrEP and other STI related topics. Results: We identified approximately 7, 574 residents across 247 residencies in 11 states. We received 217 responses to our survey, of which 203 had complete data for analysis. The majority of the sample was 25-29 years old (75%), male (53%), White (46%), and PGY-2 (48%). Twenty-one percent of the sample received formal education on PrEP. After controlling for demographic variables, residents with prior formal PrEP education were more likely to be comfortable taking sexual history from LGBTQI patients, discussing/providing PrEP, discussing PrEP efficacy, discussing PrEP monitoring, side effects, drug resistance, and adherence compared to residents who did not have formal PrEP education (Table 1). Association Between Formal PrEP Education and Comfort Levels with Discussing PrEP and other STI Related Topics Conclusion: We found a strong association between formal PrEP education and resident's confidence in discussing PrEP. Investing in formal resident education programs in the Southern region will be important in achieving the Ending the HIV Epidemic's goal of reducing new infections by 75% in 5 years and 90% in 10 years. Disclosures: Leandro A. Mena, MD, MPH, Binx Health (Grant/Research Support)Evofem (Grant/Research Support)Gilead Science (Consultant, Grant/Research Support, Speaker's Bureau)GSK (Grant/Research Support)Janssen (Grant/Research Support)Merck (Consultant, Grant/Research Support)Roche Molecular (Consultant, Grant/Research Support)SpeedDx (Grant/Research Support)ViiV Healthcare (Consultant, Grant/Research Support, Speaker's Bureau)